The dynamics of study circles: some reflections on ABIM's collaborative learning system - Baba, Sidek (Academy for Civilisational Studies, 2005)
The dearth of literature on study circle learning system available in our midst has brought our attention to this publication on the Dynamics of Study Circles: Some Reflections on ABIM's Collaborative Learning System in our monograph series, Prof. Sidek Baba, the author of this work speaks his mind in his analysis to assess the effectiveness of study circles at least for two main reasons.